2015
DOI: 10.1103/physrevlett.115.186402
|View full text |Cite
|
Sign up to set email alerts
|

Detuning-Controlled Internal Oscillations in an Exciton-Polariton Condensate

Abstract: We theoretically analyze exciton-photon oscillatory dynamics within a homogenous polariton gas in the presence of energy detuning between the cavity and quantum well modes. Whereas pure Rabi oscillations consist of the particle exchange between the photon and exciton states in the polariton system without any oscillations of the phases of the two subcondensates, we demonstrate that any nonzero detuning results in oscillations of the relative phase of the photon and exciton macroscopic wave functions. Different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…The condensate density is then no longer stationary in time. Here a plot of the polariton occupations in each trap, in figure 5(b), indicates ac Josephson-like oscillations between the detuned traps, with a running phase [20,35,47,50,51]. The TCMT and SSI exhibit excellent agreement in all three cases, which helps validate the preceding results of the two-mode TCMT.…”
Section: Comparisons With Ssisupporting
confidence: 75%
“…The condensate density is then no longer stationary in time. Here a plot of the polariton occupations in each trap, in figure 5(b), indicates ac Josephson-like oscillations between the detuned traps, with a running phase [20,35,47,50,51]. The TCMT and SSI exhibit excellent agreement in all three cases, which helps validate the preceding results of the two-mode TCMT.…”
Section: Comparisons With Ssisupporting
confidence: 75%
“…and a † ba † a ≈ a † b a † a (this assumes that the states remain coherent states), the two observables are ruled by the following equations of motion [39,46]:…”
Section: Theorymentioning
confidence: 99%
“…The polariton implementation of Josephson effects is increasingly investigated [30][31][32][33][34][35][36][37][38]. Recently, it was observed that polaritons are predisposed for Josephson physics from the very nature of their light-matter composition [39], exhibiting the internal type of such Josephson dynamics where the exchange is not between two spatially separated condensates but between the two internal degrees of freedom that make up the polariton, namely, its exciton and photon components. This is an adequate picture, since condensates of polaritons are also condensates of photons and excitons [40], with their Rabi coupling acting as the tunneling.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22]. Recently, however, also the non-interacting regime has proved to be topical, with reports of skyrmions analogues [23], band structure engineering [24] focusing and conical polariton diffraction [25], internal Bosonic Josephson junctions [26], emulates of oblique dark and half solitons [27], Z topological insulator [28] or the implementation of Hebbian learning in neural networks [29] to name a few but illustrative examples. In most of these cases, interactions bring the physics to even farther extents rather than spoiling the underlying linear effect, that remains nevertheless the one capturing the phenomenon.…”
mentioning
confidence: 99%